CAMPUR KODE DALAM INTERAKSI SOSIAL MASYARAKAT MADURA DI DUSUN PAYANGAN KECAMATAN PUGER JEMBER - Prasetiyo, Anggik Budi; Nugraha, Dana Dwi (Fakultas Bahasa dan Sastra Indoensia, 2021)
This research aims to find, understand, and then describe the code mix that exists in the interaction of the Madurese community in Payangan hamlet, Puger Kulon village, Puger. Sources of data in this study are speech events in the social interaction activities of the Madurese community in Payangan Hamlet, Puger Kulon Village, Puger. The data of this research are in the form of words, phrases, and clauses in the speech which are indicated to contain mixed codes. This study is included in the type of qualitative research using the interpretive descriptive method. Furthermore, the approach used for data analysis is a sociolinguistic approach. The results of this study indicate that there are several variations of code mixing, namely mixing Indonesian and Javanese codes. There are two factors behind the emergence of code mixing, namely the factor of representation of diction and mother tongue